Safety and Efficacy of Travoprost (0.004%) Versus Timolol (0.5%) In Patients with Open Angle Glaucoma or Ocular Hypertension: A Randomized Prospective Double-Blind Study - Prasheeta V Praviraj; Gondi Surendra Kumar; Poovizhi Kannan; P Ushakiran, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The ultimate goal of pharmacotherapy in glaucoma is to reduce the IOP. The current study is designed to audit the efficacy and safety of 0.004% travoprost over 0.5% timolol eye drops for the treatment of primary open angle glaucoma or ocular hypertension and to suggest appropriate intervention for the treatment of the disease. Methods: A prospective, randomised, double blind, parallel group clinical study was conducted among adult patients aged 18 years and above of either gender, any ethnicity clinically diagnosed with primary open angle glaucoma or ocular hypertension without any recognizable secondary causes. 60 patients were randomly assigned in double blind fashion to the treatment groups (30 were in group A intervention other 30 were in Group B intervention). Efficacy and safety were assessed on periodic follow-up visits. Results: There was no significant difference observed between the two groups in the first two weeks of follow up i.e. 2nd and 6th week. But by 9th week onwards statistically significant difference was observed. On 12th week difference was extremely statistically significant. Timolol group showed more of eye irritation (23.33%) followed by red eye in only 2 patients (6.67%). The Group B (Travoprost) patients showed eye irritation (40.7%), red eye (29.6%), Iris pigmentation (3.7%), eyelash growth (14.8%), periorbital pigmentation (3.7%). Conclusion: Travoprost 0.004% eye drops once daily lowers the intra-ocular pressure significantly more than Timolol 0.5% eye drops twice daily. Though timolol has shown better tolerability, both travoprost and timolol were well tolerated and safe for use in patients with open angle glaucoma.